PRACTICAL METHOD FOR ANALYSIS AND DESIGN OF SLENDER REINFORCED CONCRETE COLUMNS SUBJECTED TO BIAXIAL BENDING AND AXIAL LOAD (Malaysian Journal of Civil Engineering, 2018)
Reinforced and concrete-encased composite columns of arbitrarily shaped cross sections subjected to bi axial bending and axial load are commonly used in many structures. For this purpose, an iterative numerical procedure for the strength analysis and design of short and slender reinforced concrete columns with a square cross section under biaxial bending and an axial load by using an EC2 stress-strain model is presented in this paper. The computational procedure takes into account the nonlinear behavior of the materials (i.e., concrete and reinforcing bars) and includes the second order effects due to the additional eccentricity of the applied axial load by the Moment Magnification Method. The ability of the proposed method and its formulation has been tested by comparing its results with the experimental ones reported by some authors. This comparison has shown that a good degree of agreement and accuracy between the experimental and theoretical results have been obtained. An average ratio (proposed to test) of 1.06 with a deviation of 9% is achieved.